Bonded Orthodontic Retainer and Fixed Partial Denture Made with Fiber Reinforced Composite Resin - Kumbuloglu, Ovul; Saracoglu, Ahmet; Cura, Cenk; User, Atilla (European Journal of Dentistry, 2011)
Retention is the phase of orthodontic treatment which maintains teeth in their orthodontically corrected positions, following the cessation of active orthodontic tooth movement. Development of resin-impregnated, fiber-reinforced composite materials has provided the potential to develop new approaches for stabilizing teeth and replacing teeth conservatively. This case report describes the rehabilitation of a patient with orthodontic and prosthetic problems. The long-term behavior of glass fibers splint must be evaluated in clinical studies. (Eur J Dent 2011;5:237-240)
Keywords: Fixed partial denture; Orthodontic retainer; Fiber reinforced composite resins; Remineralization; Resin infiltration